1978
DOI: 10.1037/0022-0167.25.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modeling, rehearsal, feedback, and remediation on acquisition of a counseling strategy.

Abstract: This study assessed the effects of four primary components of the microcounseling training model in the acquisition of a counseling strategy. The four training components investigated were (a) written and video models; (b) roleplay practice; (c) peer feedback; and (d) role-play remediation practice. Forty beginning graduate students in counseling were assigned randomly to the following four treatment conditions: modeling; modeling and practice; modeling, practice, and feedback; and modeling, practice, feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Another possible confounding factor reported was the stage of study of the two groups of students (one medical school taught pelvic examination in the second year, and the other in the third year)-the third years were trained by the laywoman, but their communication skills may have been more advanced because they have more experience of using communication skills in practice. Other studies [41][42][43] have shown that the use of simulated patients and/or role-play produced improvements no greater than other interactive methods of training, although two studies [41,43] may not have been statistically powerful enough to detect between group differences. It should also be noted that the students in the Peters et al [41] study were told to practice the nine steps of microcounseling that had been taught before the assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another possible confounding factor reported was the stage of study of the two groups of students (one medical school taught pelvic examination in the second year, and the other in the third year)-the third years were trained by the laywoman, but their communication skills may have been more advanced because they have more experience of using communication skills in practice. Other studies [41][42][43] have shown that the use of simulated patients and/or role-play produced improvements no greater than other interactive methods of training, although two studies [41,43] may not have been statistically powerful enough to detect between group differences. It should also be noted that the students in the Peters et al [41] study were told to practice the nine steps of microcounseling that had been taught before the assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [41][42][43] have shown that the use of simulated patients and/or role-play produced improvements no greater than other interactive methods of training, although two studies [41,43] may not have been statistically powerful enough to detect between group differences. It should also be noted that the students in the Peters et al [41] study were told to practice the nine steps of microcounseling that had been taught before the assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was designed to assess both quality and quantity measures of the dependent variables. In counselor training, it is common for researchers to limt the measure of the dependent variable to a single frequency count (Bailey, Deardorff, & Nay, 1977;Frankel, 1971;Kuna, 1975;Peters, Cormier, & Cormier, 1978;Stone, 1975;Wallace, Horan, Baker, & Hudson, 1975). Research on training effectiveness by Stokes and Tait (1978), however, demonstrated that a single measure of the dependent variable would have presented a limited scope of the findings.…”
Section: Measurement Of the Dependent Variablementioning
confidence: 99%